Penile injuries: A 10-year experience - Reddy, S V Krishna; Shaik, Ahammad Basha; K, Srinivas Rao (Canadian Urological Association Journal, 2014)
We report our 10-year experience with penile injuries. We retrospectively reviewed the records of 156 cases of male external genitalia injuries between May 2002 and December 2012. Of these, only 26 patients presented without urethral injuries and were included in this study. Patients were divided into 4 groups: Group 1 (n = 12) with patients with penile fractures injuries; Group 2 (n = 5) with patients with penile amputation injuries; Group 3 (n = 2) with patients with penile penetrating injuries; and Group 4 (n = 7) with patients with penile soft tissue injuries. Grading of injury was done using the American Association for the Surgery of Trauma (AAST)-Organ injury scale of penile injury. Penile injuries without urethral injuries are urological emergencies which require immediate attention.